(3GdahGFO GdLOjOIs - (3GdHgHgGfj, GdCSJGP GdCcHQ, GdhMjO, eMeO HGbQ Hf eMeO Cced, (B1206 (3g`s
(3ChdgG (B:s
..... (3aXgQ aSGO eG WYf HYV GdZGadjf Ch GdbGUQjf Ydi GdabgGA aj PcQge GdCQcGf hCMcGegG hcPG CMcGe GdTQhW , aGFOI GYde chf GdMce JbjI EfeG gh EPG cGf ehGabG dePgH GdYGeI (B...s
(3BNQgG (B:s
.. (3aGFOI (B: (3bO hQO aj GdCNHGQ Cf GdTjYI cGfhG jbhdhf aj GdMOjK GdPj hGab GdJbjI CYWGc ef LQGH GdfhQI bjd eQGOge JTHjg GdeYUhe (B...(3Edi gPg GdMcGjI heKdG eCNhPG efgG (B. (3JeJs
(3aj HWGbI cGTa GdZWGA (B: (3CfgG ef fSN eMeO Ydj Hf eMeO WGgQ GdHMQGfj , SfI (B: 17 (3Ph GdbYOI (B1193 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\ 49s
(3GdPQjYI (B16\1529s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs